2010
DOI: 10.1128/iai.00382-10
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety Level 2 Model of Pneumonic Plague and Protection Studies with F1 and Psa

Abstract: Attenuated Yersinia pestis pgm strains, such as KIM5, lack the siderophore yersiniabactin. Strain KIM5 does not induce significant pneumonia when delivered intranasally. In this study, mice were found to develop pneumonia after intranasal challenge with strain KIM5 when they were injected intraperitoneally with iron dextran, though not with iron sulfate. KIM5-infected mice treated daily with 4 mg iron dextran died in 3 days with severe pneumonia. Pneumonia was less severe if 4 mg iron dextran was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 72 publications
1
25
0
2
Order By: Relevance
“…A mouse BSL2 model of pneumonic plague (Galván et al 2010) was used to compare the virulence of wild-type and Δ ompA Y. pestis strains. C57BL/6 mice were inoculated intranasally with equal numbers of Y. pestis KIM5 (Pgm-) and an isogenic ompA deletion strain.…”
Section: Resultsmentioning
confidence: 99%
“…A mouse BSL2 model of pneumonic plague (Galván et al 2010) was used to compare the virulence of wild-type and Δ ompA Y. pestis strains. C57BL/6 mice were inoculated intranasally with equal numbers of Y. pestis KIM5 (Pgm-) and an isogenic ompA deletion strain.…”
Section: Resultsmentioning
confidence: 99%
“…There is a need for a greater understanding of the disease process, as well as the development of new vaccine and molecular therapy candidates, and a greater understanding of the roles and functions of these candidates in Y. pestis pathogenesis. One such candidate is the chaperone/usher fimbria Psa, which recently was shown to provide incomplete but significant protection against an attenuated Y. pestis strain (20). The operon encoding this fimbria is expressed at the flea vector temperature of 26°C, but a large increase in expression is observed in the mammalian host and in vitro under mammalian host-like conditions such as a temperature shift and a low pH (24,30).…”
Section: Discussionmentioning
confidence: 99%
“…The data represent three independent experiments. The numbers of tissue samples harvested for the wild-type and ⌬psaA, ⌬caf1, and ⌬psaA ⌬caf1 mutant strains, respectively, were 20,7,14 organisms of the wild-type and ⌬psaA mutant strains, and doses ranging between 100 and 10 5 organisms of the ⌬caf1 and ⌬psaA ⌬caf1 mutant strains. The LD 50 of the wild-type strain in C57BL/6J infected by the s.c. route was determined to be ϳ1 CFU, which is consistent with previous reports ( Fig.…”
Section: Both Psaa and Caf1 Are Required For Bubonic Infectionmentioning
confidence: 99%
“…Psa has been shown to agglutinate red blood cells (9) and, like F1, to inhibit phagocytosis by macrophages (10). A number of studies have also highlighted that Psa is expressed in vivo in infected tissues (11) and plays a key role in virulence of Y. pestis (12,13). Recent studies have shown that the Psa antigen induces a robust immune response and induces significant albeit incomplete protection in a murine model of pneumonic plague (11).…”
mentioning
confidence: 99%
“…A number of studies have also highlighted that Psa is expressed in vivo in infected tissues (11) and plays a key role in virulence of Y. pestis (12,13). Recent studies have shown that the Psa antigen induces a robust immune response and induces significant albeit incomplete protection in a murine model of pneumonic plague (11). Psa has also been shown to mediate binding to cells, including human respiratory tract epithelial cells (7,9), as well as to pulmonary surfactant (5), which coats the alveolar surface of lungs.…”
mentioning
confidence: 99%